EFFECTIVENESS OF PROGRESSIVE TAX SYSTEM ON WEALTH DISTRIBUTION - Loso Judijanto; Sulaiman; Grace Kelly Hadi Putri Sihombing; Al-Amin (Adisam Publisher, 2025)
The implementation of progressive taxes in various jurisdictions and an assessment of their performance in achieving a more balanced distribution of wealth. The research method used literature, which was taken in accordance with the context of the research. The results show that the progressive tax system has potential as a wealth redistribution tool. However, its effectiveness is often hindered by the practice of tax avoidance, tax evasion, and aggressive tax planning. Political and ideological resistance also plays a role in challenging the legitimacy and revenue levels of progressive taxes. In addition, the complexity of tax administration can hinder its effectiveness, causing uncertainty and higher compliance costs for taxpayers. However, despite these challenges, the research points to administrative reform, strengthening of the legal framework, and public participation as important steps that can improve social justice through this system. The conclusion of this study is that although the progressive tax system is not perfect, with the right adjustments, it can be more effective in supporting a fairer distribution of wealth.